Studies on the miscibility of poly(isobutylene) with poly(ether imide) blends in dilute solutions - Cakar, F.; Cankurtaran, O. (NATL INST OPTOELECTRONICS, 2009)
The miscibility criteria of poly(isobutylene) (PIB) and poly(ether imide) (Ultem) were investigated at 30 degrees C in chloroform in dilute solutions by viscometric analysis. The intrinsic viscosity and viscometric parameters of this blend system were determined for several PIB/Ultem mixtures in compositions such as 80/20, 70/30, 60/40, 40/60, 20/80 in chloroform solutions. The miscibility criteria on the basis of the sign of Delta b, Delta b', Delta[eta], alpha and beta which are the difference between their experimental and ideal values were calculated by applying theoretical equations. The data obtained from the viscometry studies showed that the prepared blends were immiscible in all the studied composition ranges at 30 C. The miscibility of the mixtures was also studied by fourier transform infrared spectroscopy.
Keywords: Poly(isobutylene); Poly(ether imide); Miscibility; Viscometry; FT-IR; BISPHENOL-A; COPOLYESTER; CRITERION; ULTEM; Materials Science; Optics